THE CHALLENGES OF THE 2020 – 2035 INDONESIAN EDUCATION ROADMAP TOWARDS ACHIEVING WORLD-CLASS HIGHER: A REVIEW - Rayhana; Tjalla, Awaluddin (Jurnal Evaluasi Pendidikan, 2021)
Indonesia's 2020-2035 education roadmap towards the achievement of world-class higher education is currently dealing with the covid 19 pandemic. So that government policies are needed so that the achievement of world-class higher education can be implemented. This article discusses new policies related to the achievement of world-class higher education from the Ministry of Education and Culture of the Republic of Indonesia. In 2035, it is hoped that universities in Indonesia will not only be able to compete with other world universities, but also play an optimum role in producing superior human resources, democratic future leaders and developing sustainable research.